MOTIVASI MASYARAKAT UNTUK TIDAK MENGGUNAKAN HAK PILIH DALAM PEMILIHAN LEGISLATIF TAHUN 2009 DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Syafitri, Novika; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is to find out how motivation and classification society not to use voting rights in the legislative elections of 2009 and the classification society in the village Simpang Baru Tampan District Pekanbaru City. This research used descriptive quantitative method. The sampling method used was Proportional Random Sampling method. Furthermore a number of 42 respondents. How to use the method of data collection the questionnaire, interview and documentation, for the processing of data using quantitative descriptive method. The results of the research community following abstentions much that for reasons technical factors, technical factors, political factors, political and Ideological factors. In general such factors in the crisis of confidence in the party, don't believe legislative elections will bring changes, confused choosing too many run in the legislature, as a protest because the implementation of legislative elections in fair value is not valid, the legislative elections there will be no correlations (relationships) against the interests of the voters and did not know the legislative candidates. People have no confidence again with the members of the legislature said they were representatives of the people but in fact they are not thinking of people's conditions. This research concluded that must perform and strive to select infrastructure back as ease of administration, the massive socialization, revamping legislative Member candidacy and quantity are more concerned with the quality of the background, the experience and the most basic of appropriate personnel. Advice on problems that Researchers attributed to technical factors or Administration needed roles and maximum synergy with the work of organizing other elections such as BPS, Bapecapil. Police, Head, Head, RT and RW. Perform socialization to society about the election. Factors underlying the political determination to reorganize it to restructure Indonesia's politics is a political device or all political contestants and most importantly improving the system that set it up for the good politics in this country of Indonesia according to expectations.Keywords: Motivation, Voters and Abstentions